PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS VII B SMP NEGERI 3 MADIUN - Setio Kuncoro, Anggara; Rohman Soleh, Dwi; Trisna, Herman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to enhance grade VII B students' descriptive text writing skills at SMP Negeri 3 Madiun through the discovery learning model, while also examining its influence on student engagement. The study was prompted by students' difficulty in elaborating main ideas into sufficiently detailed descriptive sentences. A two-cycle classroom action research design was employed, with each cycle progressing through planning, action, observation, and reflection stages. Thirty-one grade VII B students participated as subjects, selected through purposive sampling based on their lowest diagnostic writing scores. Data were gathered through tests, observation, and documentation, then analyzed using both quantitative and qualitative approaches. Findings revealed a steady increase in the class mean score, from 61.25 before intervention to 70.80 after cycle I, and further to 82.30 by the end of cycle II. Classical mastery likewise expanded significantly from 28.1% to 84.4%, exceeding the 75% success threshold. Student activity also progressed, shifting from a